Comparison of the accessibility of websites of voivodeship cities in Poland - Drzewiecki, Dawid; Miłosz, Marek (Journal of Computer Sciences Institute, 2025)
This article presents the results of an analysis of the accessibility of websites of 16 voivodeship cities in Poland. The study aimed to evaluate the extent to which the websites representing voivodeship capitals comply with WCAG 2.1 standards and to compare the results. The findings indicate discrepancies in meeting the requirements, emphasizing the need to implement more effective practices to improve website accessibility.